Firm performance: From dimensions to measurement - AMARHYOUZ , Asmae; AZEGAGH , Jalal (Revue Internationale du Chercheur, 2024)
This article provides an in-depth exploration of corporate performance, surpassing conventional financial measures to encompass economic, social, and environmental dimensions. By analyzing various aspects, from strategy to human performance, it sheds light on the contradictions and interactions inherent in modern business management. Challenging the limited traditional conception of performance focused on financial indicators, the study opens up to a more nuanced perspective, considering the overall impact of corporate activities on society. Delving into the dynamics between strategy and performance, the article reveals tensions arising from conflicting strategic choices, emphasizing the importance of considering social responsibility alongside profit maximization. Particularly, the analysis of human performance highlights the crucial role of human resources in achieving organizational goals. In conclusion, the article emphasizes the need for a conceptual evolution of the term "performance" towards a holistic approach, integrating interdependent factors, urging businesses to adapt to a multidimensional landscape to ensure sustainability and make a positive contribution to society while emphasizing its main measurement tools.